2010
DOI: 10.1007/s00268-010-0444-1
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous/Incidental Cholecystectomy During Gastric/Esophageal Resection: Systematic Analysis of Risks and Benefits

Abstract: Approximately 6% of patients undergoing upper GI surgery are expected to require cholecystectomy during follow-up. Because late cholecystectomies can be performed safely and because the additional calculated morbidity for these operations is lower than the morbidity for simultaneous cholecystectomy, it cannot generally be recommended to remove a normal acalculous gallbladder during upper GI surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 82 publications
2
37
2
2
Order By: Relevance
“…Many studies reported up to 15-25 % incidence 5 years after gastric surgery [1][2][3][4][5][6] with a mean value estimated of 17 % in all studies [1][2][3][4][5][6][7]. Without a specific evidence in the literature, some authors [4,11] recommend to perform a prophylactic cholecystectomy at the time of gastric surgery, while others do not [1,7] and the decision of gallbladder management is left, to date, to each surgeon's preference.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies reported up to 15-25 % incidence 5 years after gastric surgery [1][2][3][4][5][6] with a mean value estimated of 17 % in all studies [1][2][3][4][5][6][7]. Without a specific evidence in the literature, some authors [4,11] recommend to perform a prophylactic cholecystectomy at the time of gastric surgery, while others do not [1,7] and the decision of gallbladder management is left, to date, to each surgeon's preference.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of specific data and to the presence of contrasting studies, some authors [4,11] recommend to perform a prophylactic cholecystectomy at the time of gastric surgery to avoid complications and impairment of quality of life in surviving patients, while others do not [1,7] and the decision of gallbladder management is left, to date, to each surgeon's preference.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations